2006
DOI: 10.1108/01425450610673420
|View full text |Cite
|
Sign up to set email alerts
|

Improving working lives: flexible working and the role of employee control

Abstract: PurposeThe purpose of this paper is to investigate employee perceptions of the flexibility they utilize or have available to them in an NHS Trust and relate these perceptions to the concept of control.Design/methodology/approachThe paper adopts a constructivist approach and uses semi‐structured interviews, allowing employees, in their own way, to explain what flexibility policies, and practice mean to them. The paper conducted 43 interviews and one focus group across five directorates, to include a range of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…The BHPS/Understanding Society lacks employer-reported data on availability/use of FWAs which would enable assessment of gaps in knowledge pertaining to FWA availability. Meanwhile, research should also explore the relative incidence and impact of informal flexibility, shown to offer employees greater control over the distribution of work-time (Hall and Atkinson, 2006;Atkinson and Hall, 2009). It will also be important for future research to consider the effects of the recent extension of 'right to request' in the FWRs.…”
Section: Discussionmentioning
confidence: 99%
“…The BHPS/Understanding Society lacks employer-reported data on availability/use of FWAs which would enable assessment of gaps in knowledge pertaining to FWA availability. Meanwhile, research should also explore the relative incidence and impact of informal flexibility, shown to offer employees greater control over the distribution of work-time (Hall and Atkinson, 2006;Atkinson and Hall, 2009). It will also be important for future research to consider the effects of the recent extension of 'right to request' in the FWRs.…”
Section: Discussionmentioning
confidence: 99%
“…While the perception was expressed that even informal flexibility may be unfairly allocated to women with young children, on the whole such flexibility was considered to be widely applied. This informal flexibility, or time sovereignty (Sheridan, 2004), affords a high degree of control over working time that is highly valued by employees (Hall and Atkinson, 2006).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Examples of this include compressed working weeks and flexitime schemes where employees work agreed core hours but are then permitted to arrange the balance of their working hours within certain agreed parameters. While they are flexible, in the sense that employees can reduce or vary their working time, these formal practices nevertheless impose structural and rigid solutions upon employers who are required to honour the arrangements (Hall and Atkinson, 2006).…”
Section: Research Context and Conceptsmentioning
confidence: 99%
“…For example, Richman et al () identified informal arrangements simply as those that are occasionally used, while Troup and Rose () described them as those that “were negotiated in a need‐based way with supervisors or management” (p. 474). For Hall and Atkinson (), the immediacy and responsiveness to employee needs are key, because they defined informal arrangements as the ability to alter planned working time on an ad hoc basis at short notice. Eaton () went further and referred to informal arrangements as covert arrangements outside the scope of formal policies: “Supervisors can permit more flexibility than is formally allowed, encouraging employees to take time off unofficially, so that flexibility becomes invisible to higher‐level managers” (Eaton, , p. 147).…”
Section: Background and Hypothesesmentioning
confidence: 99%